2019
DOI: 10.1155/2019/9190367
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Nonvariceal Upper Gastrointestinal Bleeding in Chinese Patients on Antithrombotic Therapy

Abstract: Objective. To assess the treatment of acute nonvariceal upper gastrointestinal bleeding (ANVUGIB) in Chinese patients on antithrombotic therapy. Methods. The clinical data of patients with ANVUGIB who underwent upper gastrointestinal endoscopy 24 h after bleeding at Beijing Anzhen Hospital, Capital Medical University, from 2016 to 2018, were analyzed retrospectively. The patients were divided into antithrombotic therapy and control groups and into high-risk (Forrest Ia, Ib, IIa, and IIb) and low-risk (Forrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Forrest classification was as follows: Ia spurting bleeding, Ib oozing bleeding, IIa nonbleeding visible vessel, IIb an adherent clot, IIc flat pigmented spot, and III clean base ulcer. The sites of bleeding were classified as the esophagus, stomach, and duodenum according to the gastroscopy results [10]. Some scoring systems have been developed to predict bleeding outcomes for patients with ANVUGIB bleeding.…”
Section: Forrest Classificationmentioning
confidence: 99%
“…Forrest classification was as follows: Ia spurting bleeding, Ib oozing bleeding, IIa nonbleeding visible vessel, IIb an adherent clot, IIc flat pigmented spot, and III clean base ulcer. The sites of bleeding were classified as the esophagus, stomach, and duodenum according to the gastroscopy results [10]. Some scoring systems have been developed to predict bleeding outcomes for patients with ANVUGIB bleeding.…”
Section: Forrest Classificationmentioning
confidence: 99%
“…20,21 Additionally, the degree of this small bowel mucosal injury was greater in elderly patients taking ECA than middle-aged patients. 10 In another case control study, the risk of upper GI complications was similar for both ECA and non-ECA. So, the authors concluded that the coating did not adjust the effect of aspirin.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanisms by which aspirin causes GI mucosal damage are thought to be by both direct topical injury on the epithelium and mainly, a systemic effect associated to prostaglandin depletion. 9,10 Different research has mentioned the risk factors for aspirin-induced GI complications, such as higher aspirin dose, advanced age, history of peptic ulcer disease, use of combinations of non-steroidal antiinflammatory drugs and concomitant use of drugs such as steroids or anticoagulants. 11,12 There are mechanisms used to diminish aspirinassociated GI injury, like reducing the dose of aspirin 6,13 and use of aspirin with a gastro-protective agents like proton pump inhibitors.…”
Section: Introductionmentioning
confidence: 99%